Maqasid Syariah-based Ethics In Law And Syariah Programmes In Higher Education: Guarding Emerging Technology - Syahirah Abdul Shukor; Noor Dzuhaidah Osman; Muhammad Iqbal Juliansyahzen (Penerbit USIM, 2024)
Non-Indexed Publication